Sustainability, environmental performance and disclosures - Freedman, Martin; Jaggi, Bikki (Emerald, 2010)
Accounting as an academic discipline has not made any real strides in addressing social and environmental concerns facing this planet. Since the first volume of the series was published in 2000, there have been no changes in the focus of accounting and it is still taught and practiced in the same way. Social/environmental/sustainability accounting is still a fringe subject despite the fact that ignoring environmental issues has serious consequences for the survival of this planet. Unless social and environmental accounting is formally recognized, firms will continue to view it as a means to convey information that enables them to manage their reputation without actually making any real efforts to improve the environment. The papers included in this volume discuss different aspects of sustainability, environmental performance, and environmental disclosures. Overall, it is fairly obvious from these papers that firms are aware of the impact of their activities on the environment. Some of the papers analyze what firms do about environmental issues and how these activities and their impact on the environment are disclosed in the financial statements. Though the papers come to different conclusions, it becomes clear from these studies that firms have problems in managing the impact of their environmental activities as well as in disclosing full and realistic information on these activities. Thus, it appears from these papers that firms manage their message to look good to outsiders.
Keywords: Environmental auditing.; Disclosure of information.; Sustainable development.; elektronické knihy; electronic books